KEKERASAN DALAM RUMAH TANGGA PERSPEKTIF ISLAM - Zulkifli Zulkifli (Raheema, 2019)
Data from the field shows that the number of violence against women, especially in the household continues to increase from time to time. Domestic violence (Kekerasan Dalam Rumah Tangga [KDRT]) is one proof of gender equality and justice not being realized. It is generally understood that one of the important factors that support and even enrich the practice of domestic violence is religious teachings, especially Islamic teachings contained in the Koran and Hadith. The basic question raised in this paper is: is it true that the Qur'an and the hadith teach about domestic violence? By using the literature study method, it is found that there has been a interpretation of gender bias in interpreting the verses and hadiths related to hitting a wife who is indicative of nusyuz. The verses of the Qur'an and the traditions of the Prophet do not justify committing acts of violence against wives and women in general. Thus, the source of domestic violence is not sourced from the Qur'an and the hadith of the Prophet. The source is the understanding of scholars (ulama) who are gender biased. Therefore, a new perspective is needed in interpreting the verses of the Qur'an and the traditions of the Prophet towards understanding the teachings of Islam with gender justice. Data dari lapangan menunjukkan angka kekerasan terhadap perempuan, khususnya di dalam rumah tangga terus meningkat dari waktu ke waktu. Kekerasan dalam rumah tangga (KDRT) merupakan salah satu bukti belum terwujudnya kesetaraan dan keadilan jender. Umum dipahami bahwa salah satu faktor penting yang mendukung bahkan menyuburkan praktik KDRT adalah ajaran agama, khususnya ajaran Islam yang terdapat di dalam Alquran dan hadis. Pertanyaan mendasar yang diajukan dalam tulisan ini adalah: benarkan Alquran dan hadis mengajarkan tentang KDRT? Dengan menggunakan metode kajian pustaka, ditemukan bahwa telah terjadi tafsir bias jender dalam memaknai ayat-ayat dan hadis yang terkait dengan memukul istri yang terindikasi nusyuz. Ayat-ayat Alquran dan hadis-hadis Nabi tidak membenarkan melakukan tindak kekerasan terhadap isteri dan perempuan pada umumnya. Dengan demikian, sumber perilaku KDRT bukanlah bersumber dari Alquran dan hadis Nabi. Sumbernya adalah pada pemahaman para ulama yang bias jender. Oleh karena itu, diperlukan cara pandang baru dalam memaknai ayat-ayat Alquran dan hadis-hadis Nabi menuju pemahaman ajaran Islam yang kerkeadilan jender.